MEDIATING ROLE OF EMPLOYEE TURNOVER INTENTIONS IN THE RELATIONSHIP BETWEEN STRATEGIC HRM, ORGANIZATIONAL LEARNING CULTURE, AND JOB SATISFACTION IN THE SHANGHAI TECHNOLOGY SECTOR - Xiong Xu; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
This study examines the pivotal role of employee turnover intentions in mediating the relationship between strategic human resource management (HRM), organizational learning culture, and job satisfaction within Shanghai's technology sector. Utilizing a quantitative approach, the research integrates responses from a comprehensive questionnaire distributed across various tech firms in Shanghai. The findings reveal that strategic HRM and a robust organizational learning culture significantly enhance job satisfaction, which in turn influences perceived organizational performance. Moreover, employee turnover intentions serve as a critical mediator, linking HRM and learning culture with job satisfaction and organizational success. This study contributes to the strategic HRM literature by highlighting how turnover intentions can impact the efficacy of HR practices and learning culture in fostering organizational resilience and employee retention in a competitive technological environment.